Gabapentin: Clinical Use and Pharmacokinetics in Dogs, Cats, and Horses - Federica Di Cesare; Viviana Negro; Giuliano Ravasio; Roberto Villa; Susanna Draghi; Petra Cagnardi (Animals, 2023)
Gabapentin is an anticonvulsant drug, which presents an established clinical efficacy in human patients for the management of refractory partial seizures, secondarily generalized tonic-clonic seizures, and for the control of chronic neuropathic pain. Gabapentin was synthesized as a structural analogue of the inhibitory neurotransmitter GABA, with GABA-mimetic effects, able to cross the blood–brain barrier. In veterinary medicine, is extra-label used in combination with other treatments to control seizures when other drugs are no longer effective or become toxic or for neuropathic pain treatment and anxiety. This review aimed to clarify gabapentin use and pharmacokinetic aspects to promote conscious use in dogs, cats, and horses. In dogs, gabapentin was beneficial in the treatment of epilepsy, as well as chronic, neuropathic, and post-operative pain, as well as anxiety. In cats, it showed efficacy in post-ovariohysterectomy-related pain and in anxiety management. In horses, gabapentin has been administered as an analgesic for chronic pain management. In conclusion, when used in combination with other drugs, gabapentin can be considered an interesting therapeutic option for the treatment of neuropathic diseases and analgesia in postoperative and chronic pain. However, despite its beneficial use in different clinical settings, further trials and pharmacokinetic studies are needed for the definition of an effective dosage regimen through proper pharmacokinetic/pharmacodynamic correlation in dogs, cats, and horses.